Analisis Keamanan Kapal Perikanan Tangkap Pukat Cincin yang Berpangkalan di PPI Desa Waai Berdasarkan Parameter Desain - Obed Metekohy (Industrial Engineering Study Program, Pattimura University, 2024)
The fishing operations of ring seine fishing boats in Waai Village, in the waters of Banda, Seram, and Haruku Strait, present promising opportunities with abundant fish stocks. However, the extreme weather conditions in the fishing grounds pose significant challenges to the fishing operations, particularly due to inadequate fishing facilities. The design and construction of the boats play a crucial role in influencing operational characteristics, especially during the processes of setting, pursing, hauling, and while the boats are en route to and from the fishing grounds. This study aims to analyze the design of ring seine boats based at the Fish Landing Base (PPI) in Waai Village, focusing on the main dimensional ratio, hull form coefficient, and static stability of the boats. The primary objective is to improve the efficiency of fishing operations and ensure the safety of fishermen at sea. The method used in this research is a survey method, with a sample of eight ring seine boats. The results of the study show design characteristics with a main dimension ratio of 37.50%, hull form coefficient of 65.62%, and a metacentric height stability value of 25%, which meet the standard design requirements for static stability. However, the rolling period value of 62.50% does not meet the standard, indicating that improvements in boat design are necessary to enhance stability.